A Janus protein-based nanofabric for trapping polysulfides and stabilizing lithium metal in lithium–sulfur batteries. Issue 15 (2nd April 2020) - Chen, Min; Chen, Zhiping; Fu, Xuewei; Zhong, Wei-Hong
Abstract : A protein-based, low-resistance Janus nanofabric is designed and fabricated for simultaneously trapping polysulfides and stabilizing lithium metal. Abstract : The shuttling of polysulfides and uncontrollable growth of lithium dendrites remain the most critical obstacles deteriorating the performance and safety of lithium–sulfur batteries. The separator plays a key role in molecule diffusion and ion transport kinetics; thus, endowing the separator with functions to address the two abovementioned issues is an urgent need. Herein, a protein-based, low-resistance Janus nanofabric is designed and fabricated for simultaneously trapping polysulfides and stabilizing lithium metal. The Janus nanofabric is achieved via combining two functional nanofabric layers, a gelatin-coated conductive nanofabric (G@CNF) as a polysulfide-blocking layer and a gelatin nanofabric (G-nanofabric) as an ion-regulating layer, into a heterostructure. The gelatin coating of G@CNF effectively enhances the polysulfide-trapping ability owing to strong gelatin–polysulfide interactions. The G-nanofabric with exceptional wettability, high ionic conductivity (4.9 × 10 −3 S cm −1 ) and a high lithium-ion transference number (0.73) helps stabilize ion deposition and thus suppresses the growth of lithium dendrites. As a result, a Li/Li symmetric cell with the G-nanofabric delivers ultra-long cycle life over 1000 h with very stable performance. Benefiting from the synergistic effect of the two functional layers of the Janus nanofabric, the resulting Li–S batteries demonstrate excellent capacity, rate performance and cycling stability ( e.g. initial discharge capacity of 890 mA h g −1 with a decay rate of 0.117% up to 300 cycles at 0.5 A g −1 ).